2015
DOI: 10.1007/s00426-015-0681-x
|View full text |Cite
|
Sign up to set email alerts
|

Congruency sequence effects and previous response times: conflict adaptation or temporal learning?

Abstract: In the present study, we followed up on a recent report of two experiments in which the congruency sequence effect -the reduction of the congruency effect after incongruent relative to congruent trials in Stroop-like tasks -was observed without feature repetition or contingency learning confounds. Specifically, we further scrutinized these data to determine the plausibility of a temporal learning account as an alternative to the popular conflict adaptation account. To this end, we employed a linear mixed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(123 citation statements)
references
References 51 publications
9
109
5
Order By: Relevance
“…If the rhythm is broken (e.g., not enough evidence for a response when the threshold is temporarily lowered), then responding is slower. In previous work, it was demonstrated that this mechanism is important for simulating several findings in the cognitive control literature (see Schmidt, 2013c;Schmidt & Weissman, 2016) and also proves important for mixing costs. No changes were made to this mechanism in the present work.…”
Section: (Figure 1)mentioning
confidence: 79%
See 3 more Smart Citations
“…If the rhythm is broken (e.g., not enough evidence for a response when the threshold is temporarily lowered), then responding is slower. In previous work, it was demonstrated that this mechanism is important for simulating several findings in the cognitive control literature (see Schmidt, 2013c;Schmidt & Weissman, 2016) and also proves important for mixing costs. No changes were made to this mechanism in the present work.…”
Section: (Figure 1)mentioning
confidence: 79%
“…Typically entirely new models or variations of old models are used for each simulated dataset. Related to our fixed-model philosophy, we also ensured that the current version of the model is able to simulate the findings that the older versions of the model were able to simulate, namely item-specific proportion congruent effects (Schmidt, 2013a), list-level proportion congruent effects (Schmidt, 2013c), congruency sequence (or Gratton) effects (Schmidt & Weissman, 2016), and asymmetric list shifting effects (Schmidt, 2016a). For brevity, these results are presented in Appendix B, but further details can be obtained in the original papers or from the lead author on request.…”
Section: Backwards Compatibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…One potential interpretation of this effect is conflict adaptation: following a conflicting incongruent trial, attention to the word is diminished (e.g., Botvinick et al, 2001). Another potential interpretation is temporal learning: congruency effects are larger following a fast congruent LIST-LEVEL PROPORTION CONGRUENT EFFECT 25 trial than following a slow incongruent trial (see Schmidt & Weissman, 2016). The current paradigm might thus be adjusted to pit these two accounts against one another.…”
Section: Implications For Future Workmentioning
confidence: 99%